Critical Analysis of the Risks in the Use of the Internet and Social Networks in Childhood and Adolescence - Núñez-Gómez, Patricia; Larrañaga, Kepa Paul; Rangel, Celia; Ortega-Mohedano, Félix (Frontiers in Psychology, 2021)
Kids are people who consume content on the Internet very frequently and actively participate in social networks, so it is necessary to know the risks of their use by children and adolescents, in order to propose a critical analysis of them. This work is the result of two research studies: a qualitative and a quantitative analysis of 1,350 children and adolescents between 6 and 12 years old living in Spain. The objectives of this paper are analysing the attitudes of children and adolescents about the safe use of the Internet and social networks, studying the differences in the discourse of children and adults about the risks of their use, as well as defining areas for improvement to promote the safe use of the Internet and social networks. The main findings include intergenerational tensions between adults and children in the use of the Internet, the difficulty of reaching consensus and quality support when using the Internet. Children have transcended the physical and digital space considering it, so they must be given the tools, competences and security to fully develop their digital identity.